Prevalence of Foreign Body in Ear, Nose, and Throat inImam Khomeini hospital, Iran - Azam Fazlipour; Mahammad Hossein Toloei (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background and Objectives: Otolaryngologists usually encounter foreign bodies pediatricians, and preliminary care physicians. In this study,determining the prevalence of foreign body types in the ear, nose, and throat is the goal.Methods: This study is a descriptive-analytic kind of study based on hospital information that was taken from patients with foreign bodies in ear, throat, and nose referred to ENT Emergency Department of Imam Khomeini Hospital in Ahvazduring 1396 and 1397.Registered hospital records are used to determine the number of patients with foreign bodies in the ear, throat, and nose. Also, Socio-demographic data were collected prospectively using a pre-designed questionnaire. Descriptive and analytical statistical methods (using SPSS version 22.0) were used to input and analyze data collected from 4257 patients. Conclusion: Foreign bodies in the ears, nose, or throat are frequent in the emergency services of otorhinolaryngology (ENT). The most common site of FB accommodation is in the Throat. FB of the ear, nose, and throat should be handled properly to avoid complications.